Empirical Research on Digital Literacy in English Education in Indonesian Setting in Recent 10 Years - Ratna Dewanti; Parlindungan Pardede (Journal of English Teaching, 2022)
Due to its crucial significance to function in today's globally e-interpenetrated, schools are supposed to be the first institution to accelerate digital literacy competence improvement. To meet the challenge, English educators are in a strong position to contribute significantly due to the natural close link between language and digital literacy and the status of English as the current first global language. Like in other skills development programs, digital literacy skills development considerably depends on serious methodological and theoretical research. This systematic review aims at portraying the trends of research in the last decade on digital literacy integration in English Education (EE) in Indonesian context in terms of yearly distribution, research designs, research focuses, data collection methods, and the educational levels of the setting. To serve the aims, some databases were searched, through which 66 research articles were obtained. The results showed that digital literacy research in the field is still new, but it keeps on proliferating since 2020. The predominant research designs are case study and survey. Major focuses are related to the instrumental aspect of digital literacy. The studies were set at higher learning, senior high school, and junior high school levels, and none were set at the primary school level. This paper ends with recommendations for further research and for actual enactments.